The SPIRITUALITY AND STRESS: BIBLIOMETRIC ANALYSIS OF THE CURRENT STATE OF THE ARTICLES AND PERSPECTIVE: SPIRITUALITAS DAN STRES: ANALISIS BIBLIOMERIK TERHADAP STATUS ARTIKEL DAN PERSPEKTIF TERKINI - Rahmadany, Muhammad Fa'iz; Munawaroh, Siti; Wiyono, Nanang; Hastami, Yunia (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2022)
Introduction: to learn more about and comprehend the most recent studies on spirituality and stress. This study assesses pertinent themes connected to spirituality and stress through bibliometric analysis using the keyword "spirituality and stress" as input. Methods: The Scopus database was chosen in this study since bibliometric analysis thought it was the best. The bibliometric analysis tool VOSviewer software was also used to show a network of authors, nations, journals, and keywords. On September 26, 2022, an analysis based on the most recent five years of publishing, article-type papers, and journal-sourced data from 2017 to the current day discovered a total of 829 documents. Result: The results showed that in the last 5 years, the number of publications of articles on spirituality and stress has grown significantly and experienced a dynamic development. The USA is the country with the most article publications in the world with lead authors, and research institutes involved. Duke University Medical Center became a prominent journal with regular publications. Conclusion: The bibliometric analysis presented provides relevant information related to the theme studied, namely spirituality and stress.